The Legal Consequences of Divorce on Joint Assets in the Religious Courts - Komarudin Komarudin; Akhmad Khisni; Amin Purnawan (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to find out and explain the legal consequences of divorce on joint property in religious courts. To find out and explain the obstacles due to divorce law on joint property in religious courts. The method used by the researcher is Juridical Empirical (socio-legal research) and the specifications in this study are descriptive analytical. Based on the results of the study that resulting in marital property controlled by the husband without the consent of the ex-wife cannot/is not allowed to sell or transfer the property without the consent of the ex-wife. The obstacle: shows that there is still a lack of public understanding of the applicable legal provisions governing assets in marriage. Economic factors. Factors of objects or objects (Joint Asset or Gono-Gini property). The responsibility factor of the parties (husband and wife). The solution: the need for legal counseling to the community and the prospective brides who will carry out the marriage. The settlement can be through the village head, but if it cannot be resolved through the village head then through the court institution by attaching a certificate of incapacity (prodeo). The settlement of one of the selling parties must be reduced by the distribution of the value of the price of the goods sold. The settlement in this case is that the collateralized object is confiscated and auctioned by the bank as the creditor who provides the debt facility.